Oman in the parliamentary sessions of the Iraqi Council of Representatives (1945-1958) (Journal of the College of Basic Education, 2022)
The parliamentary sessions of the Iraqi Council of Representatives enjoyed extensive discussions that dealt with Iraq's internal situation and its foreign policy in the Arab and international arenas, despite the Iraqis' preoccupation with their difficult economic situation, which was exacerbated by the results of the Second World War, which was reflected in their daily living.